Experimental and Theoretical Investigation on the Thermo-Mechanical Properties of Recycled Aggregate Concrete Containing Recycled Rubber - Tang, Yunchao; Feng, Wanhui; Chen, Zheng; Nong, Yumei; Yao, Minhui; Liu, Junhui (Frontiers in Materials, 2021)
The utilization of recycled aggregates made from construction wastes and recycled rubber made from waste tires is an effective method to realize the sustainable development. Thus, this study aims to determine the feasibility of using recycled aggregate concrete containing rubber, named rubberized recycled aggregate concrete (RRAC) as a new type of green-building material. The experimental carbon emissions test verified RRAC as a low-carbon material. In addition, the residual mechanical properties of RRAC were investigated under elevated temperatures. After exposure at 200, 400, and 600 °C for 60 min, the stress−strain curve, compressive strength, energy absorption capacity, and spalling resistance of RRAC with recycled aggregate replacement ratios of 50% and 100%, rubber contents of 0%, 5%, 10%, and 15% were explored with microstructural analysis. Moreover, empirical models were proposed to describe the effects of heated temperatures and rubber contents on the stress–strain relationship of RRAC. The results indicated that the rubber particles could reduce the spalling of specimens based on the vapor pressure theory. Therefore, this study provided scientific guidance for the design of structures made with RRAC for resisting high temperatures.